Children first: women’s perspectives on evacuation at Fuego volcano and implications for disaster risk reduction - Bartel, Beth A.; Naismith, Ailsa K. (Frontiers in Earth Science, 2023)
Cultural norms are major drivers of behavior during crisis. Gender norms influence how disasters caused by natural hazards differentially affect women, men, and other gender identities around the world, and how these people differently approach disaster risk reduction strategies involving decision-making and evacuation. At Fuego volcano, Guatemala, we applied qualitative methods to investigate women's experiences of the evacuation process after a paroxysmal eruption on 7-8 March, 2022. While participants' experiences and decisions varied, we found that gendered norms drive many of the evacuation dynamics within communities at Fuego volcano, including who evacuates and who decides at the community and household levels. We find that women are prioritized for evacuation with the children and elderly in their care yet men are prioritized in the decision-making; that despite this hierarchy, a woman may override a male partner's decision in order to prioritize the safety and well-being of her children; and that even if she overcomes social barriers to leaving, she may be unable to evacuate in a timely manner because of lack of transportation. This gendered evacuation strategy disproportionately leaves men exposed to the threat and places the burden of evacuation with large families on the women. This study contributes an example of how gendered norms impact disaster risk reduction strategy at an active volcano and how understanding gendered experiences of evacuation can inform future disaster risk reduction efforts.